Arabic Learning Analysis Using the Qira'ah Kitabah Method to Improve Students' Learning Skills - Agustini, Agustini (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2025)
This study aims to analyze the effectiveness of the Qira'ah Kitabah method in Arabic language learning to improve the learning skills of tenth-grade students at MAN 1 Gunungkidul. The Qira'ah Kitabah method, which integrates reading (qira'ah) and writing (kitabah) skills, is considered capable of encouraging students to be more active in understanding the structure of the Arabic language contextually. This research uses a qualitative approach with a case study design. The subjects of the study are Arabic language teachers and tenth-grade students who participated in learning with this method. Data collection techniques include observation, in-depth interviews, and analysis of student learning documents. The results of the study indicate that the implementation of the Qira'ah Kitabah method can increase learning motivation, strengthen vocabulary understanding, and improve students' reading and writing skills in Arabic. Supporting factors for the success of this method include active student involvement, contextual learning media, and the communicative approach used by the teacher. This research recommends the broader application of the Qira'ah Kitabah method as an effective alternative strategy for Arabic language learning at the Madrasah Aliyah level.